2014
DOI: 10.1002/ange.201406521
|View full text |Cite
|
Sign up to set email alerts
|

The Optimally Performing Fischer–Tropsch Catalyst

Abstract: Microkinetics simulations are presented based on DFT‐determined elementary reaction steps of the Fischer–Tropsch (FT) reaction. The formation of long‐chain hydrocarbons occurs on stepped Ru surfaces with CH as the inserting monomer, whereas planar Ru only produces methane because of slow CO activation. By varying the metal–carbon and metal–oxygen interaction energy, three reactivity regimes are identified with rates being controlled by CO dissociation, chain‐growth termination, or water removal. Predicted surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 53 publications
1
61
0
Order By: Relevance
“…We already showed that the FT reaction has several kinetic regimes and the Rucatalyzed FT reaction operates in a kinetic regime, where CO dissociation is not controlling the overall rate. 23 This is supported by the results in Figure 5, where it can be seen that the surface stability of CO does not influence the chain-growth probability. The interesting consequence is that, when CO dissociation is not rate-controlling, an increase in the number of free surface sites does not necessarily increase the overall CO consumption rate and the chain-growth probability.…”
Section: Resultssupporting
confidence: 79%
“…We already showed that the FT reaction has several kinetic regimes and the Rucatalyzed FT reaction operates in a kinetic regime, where CO dissociation is not controlling the overall rate. 23 This is supported by the results in Figure 5, where it can be seen that the surface stability of CO does not influence the chain-growth probability. The interesting consequence is that, when CO dissociation is not rate-controlling, an increase in the number of free surface sites does not necessarily increase the overall CO consumption rate and the chain-growth probability.…”
Section: Resultssupporting
confidence: 79%
“…Energy reference is CO and H 2 in gas phase. 110 CH-CH recombination is lower than the overall activation barrier for CHC formation via CO insertion because of the high C-O bond cleavage activation energy. Hence the carbide chain growth mechanism will dominate.…”
Section: In Summarymentioning
confidence: 98%
“…The reaction is endothermic by 60 kJ mol À1 . On the open Ru surface, Filot et al 110 report activation energy of the CO with ''CH'' reaction to be 60 kJ mol À1 , which is 30 kJ mol À1 endothermic. The effective rate constant for chain growth termination though requires at least one additional hydrogen addition step (see Fig.…”
Section: C-c Bond Formation and Chain Terminationmentioning
confidence: 99%
“…Experimental approaches using model catalysts, co-feeding studies or transient techniques have been used to obtain insights into mechanistic details of the Fischer-Tropsch chain growth reaction [18][19][20][21]. More recently, theoretical calculations using ideal surface structures have been used to study the mechanism on the molecular level [8,22,23]. The experimental counterpart of this, surface science using single crystal surfaces, has rarely been employed for the cobalt system, although there are many opportunities for decisive studies on relevant elementary steps in the mechanism, particularly if such experiments are complemented by state-of-the-art computational studies [24].…”
Section: Introductionmentioning
confidence: 99%